Religious Dynamics and Transitions in Brazil: Insights from National Census Data - Ribeiro da Silva, Michael Ruberson (International journal of Latin American religions, 2025)
Brazil's religious landscape has undergone substantial changes over the past 150 years. Historically dominated by Roman Catholicism, the country has become increasingly pluralistic, with rising numbers of Evangelicals, Spiritists, Afro-Brazilian religions, and individuals with no religion. This study examines these long-term trends using comprehensive census data. A time-series analysis was conducted using data from eleven national censuses (1872-2022). Descriptive statistics and Joinpoint regression were applied to identify significant changes in religious affiliation. Intercensal percentage changes, absolute changes, and trend slopes were calculated for major religious groups. The analysis of Brazilian census data from 1872 to 2022 revealed significant shifts in religious affiliation. Roman Catholicism, which accounted for 99.7% of the population in 1872, declined to 56.7% in 2022. In contrast, Evangelicals increased from virtually zero to 26.9%, while the percentage of people with no religion rose to 9.3%. Smaller but consistent increases were also observed in Spiritism, Afro-Brazilian religions, and other minority groups. Joinpoint regression identified statistically significant inflection points, notably in 1980, when Catholic decline accelerated and Evangelical growth intensified. This study offers a comprehensive overview of Brazil's religious transformation over 150 years using official census data. It identifies long-term declines in Catholic affiliation, significant growth in Evangelicalism, and rising numbers of non-religious people. The findings provide a valuable baseline for future research and underscore the role of census data in tracking large-scale religious transformations. The study also revealed differences between institutional estimates from Vatican statistics and self-declared Catholic affiliation from census data.